2012
DOI: 10.1002/pssc.201200454
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of oxygen chemical diffusion in PuO2‐x and analysis of oxygen diffusion in PuO2‐x and (Pu,U)O2‐x

Abstract: All available oxygen potential-temperature-composition data for the calcium fluorite-structure ** phase were retrieved from the literature and utilized in the development of a binary solid solution representation of the phase. The data and phase relations are found to be best described by a solution of [Pui^C^] and [PuO 2 ] with a temperature dependent interaction energy. The fluorite-structure is assumed to be represented by a combination of the binaries' and CUO^^, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In the PuO 2-x , it is reported that sources of electrical conductivity is not ions but electrons and holes [10]. The electrical conductivity 𝝈 is written by, 𝝈 = 𝝈 𝒆 𝝈 𝒉 = 𝝁 𝒆 𝐡 𝝁 𝒉 (14) with 𝝈 = 𝝁 and 𝝈 𝒉 = 𝐡 𝝁 𝒉 , where 𝝁 and 𝝁 𝒉 are electrons and holes mobility, respectively. Since = 𝟐 𝐎 , Equation 15 is derived using Eqs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the PuO 2-x , it is reported that sources of electrical conductivity is not ions but electrons and holes [10]. The electrical conductivity 𝝈 is written by, 𝝈 = 𝝈 𝒆 𝝈 𝒉 = 𝝁 𝒆 𝐡 𝝁 𝒉 (14) with 𝝈 = 𝝁 and 𝝈 𝒉 = 𝐡 𝝁 𝒉 , where 𝝁 and 𝝁 𝒉 are electrons and holes mobility, respectively. Since = 𝟐 𝐎 , Equation 15 is derived using Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data on the oxygen chemical diffusion coefficient 𝐷 ̃ in PuO 2−x is limited. Bayoglu and Lorenzelli [13] reported 𝐷 ̃ to be about 1×10 −6 cm 2 /s at 1353 K. Kato et al [14] obtained the value of 10 −7 cm 2 /s at temperatures in the range of 1473-1873 K. A large difference was observed between the reported data. Bayoglu and Lorenzelli [13] measured 𝐷 ̃ during the oxidation process.…”
Section: Oxygen Diffusion Coefficientsmentioning
confidence: 92%
See 2 more Smart Citations
“…10,12,13 The stoichiometry of PuO 2 is known to have a signicant impact on important physical properties like lattice parameters, thermodynamical stability, and melting temperature. 14 Therefore, it is essential to investigate the characteristics of defects in non-stoichiometric PuO 2 composition to understand the variation in its physical properties.…”
Section: Introductionmentioning
confidence: 99%